Krill oil supplementation in vivo promotes increased fuel metabolism and protein synthesis in cultured human skeletal muscle cells - Katare, Parmeshwar B.; Dalmao-Fernandez, Andrea; Mengeste, Abel M.; Navabakbar, Farnaz; Hamarsland, Håvard; Ellefsen, Stian; Berge, Rolf K.; Bakke, Hege G.; Nyman, Tuula Anneli; Kase, Eili Tranheim; Rustan, Arild C.; Thoresen, G. Hege (Frontiers in Nutrition, 2024)
Krill oil is a dietary supplement derived from Antarctic krill; a small crustacean found in the ocean. Krill oil is a rich source of omega-3 fatty acids, specifically eicosapentaenoic acid and docosahexaenoic acid, as well as the antioxidant astaxanthin. The aim of this study was to investigate the effects of krill oil supplementation, compared to placebo oil (high oleic sunflower oil added astaxanthin), in vivo on energy metabolism and substrate turnover in human skeletal muscle cells. Skeletal muscle cells (myotubes) were obtained before and after a 7-week krill oil or placebo oil intervention, and glucose and oleic acid metabolism and leucine accumulation, as well as effects of different stimuli in vitro, were studied in the myotubes. In vivo intervention with krill oil increased oleic acid oxidation and leucine accumulation in skeletal muscle cells, however no effects were observed on glucose metabolism. The krill oil-intervention-induced increase in oleic acid oxidation correlated negatively with changes in serum low-density lipoprotein (LDL) concentration. In addition, myotubes were also exposed to krill oil in vitro. The in vitro study revealed that 24 h of krill oil treatment increased both glucose and oleic acid metabolism in myotubes, enhancing energy substrate utilization. Transcriptomic analysis comparing myotubes obtained before and after krill oil supplementation identified differentially expressed genes associated with e.g. glycolysis/gluconeogenesis, metabolic pathways and calcium signaling pathway, while proteomic analysis demonstrated upregulation of e.g. LDL-receptor in myotubes obtained after the krill oil intervention. These findings suggest that krill oil intervention promotes increased fuel metabolism and protein synthesis in human skeletal muscle cells, with potential implications for metabolic health.